One Tool for Many Jobs: Divergent and Conserved Actions of Androgen Signaling in Male Internal Reproductive Tract and External Genitalia - Amato, Ciro M.; Yao, Humphrey H-C.; Zhao, Fei (Frontiers in Endocrinology, 2022)
In the 1940s, Alfred Jost demonstrated the necessity of testicular secretions, particularly androgens, for male internal and external genitalia differentiation. Since then, our knowledge of androgen impacts on differentiation of the male internal (Wolffian duct) and external genitalia (penis) has been drastically expanded upon. Between these two morphologically and functionally distinct organs, divergent signals facilitate the establishment of tissue-specific identities. Conversely, conserved actions of androgen signaling are present in both tissues and are largely responsible for the growth and expansion of the organs. In this review we synthesize the existing knowledge of the cell type-specific, organ specific, and conserved signaling mechanisms of androgens. Mechanistic studies on androgen signaling in the Wolffian duct and male external genitalia have largely been conducted in mouse model organisms. Therefore, the majority of the review is focused on mouse model studies.